Financial Management Practices of Instructors of Catholic Higher Education Institutions in The Cagayan Valley Region: Basis for Financial Wellness Program - Karen Joy Catacutan; Fe Rose-Anne Maramag (Education Policy and Development, 2025)
This study investigates the financial management practices of instructors at Catholic higher education institutions in the Cagayan Valley Region. The study employs a mixed-methods approach to examine budgeting, recordkeeping, financial control, and cash management practices. The study used a descriptive survey for quantitative research and basic qualitative research for qualitative research. A total of 269 instructors participated in the study, which was conducted from January to June 2023. Quantitative data were analyzed using descriptive statistics, whereas qualitative insights were derived through thematic analysis. The findings indicate that budgeting and financial control are often practiced, whereas recordkeeping and cash management are sometimes practiced. Differences in financial management practices were noted across demographic profiles. This study highlights the need for financial wellness programs to address gaps in financial literacy and promote effective financial management practices among educators.